Building luxury brands: analyzing engagement drivers on instagram - Birkelbach, Max Jakob (2023)
Luxury brands are increasingly targeting younger generations, with social media platforms like Instagram playing a crucial role. However, little research has been conducted on the factors driving engagement on luxury brands' Instagram accounts. This study examines two groups of drivers - posting strategy and account presence - and their impact on engagement rates. Through linear regression, it is found that several variables from both groups have a significant positive effect on engagement rates. These findings offer valuable insights for luxury brands to enhance engagement and effectively engage with their future customer base.